金属基V带的新结构 - 梁锡昌; 王光建; 张博 (Jixie chuandong)
Aiming at developing present status and its limitationg of the V-belt, two new types of V-belts; Sheet-metal-style rope V-belt and steel column rope V-belt are proposed in this paper and the structure and principle and so on are also analyzed.